Diversity elements on maternal-fetal medicine fellowship websites: opportunity for improvement in recruitment and representationAJOG Global Reports at a Glance - Veronica L. Winget, MD, MS; Amanda M. Mcwhirter, MD; Marisa L. Delgado, BS; Marisa D. Tran, BS; Celia P. Valenzuela, MD; Teresa A. Orth, MD, PhD (Elsevier, 2023)
BACKGROUND: There has been a fundamental shift in the recruitment of medical students and trainees into residency and fellowship programs during the COVID-19 pandemic. Historically, websites for medical trainees demonstrate a lack of explicit focus on diversity, equity, and inclusion. Diversity has positive associations with improving healthcare team performance, patient care, and even financial goals. A lack of diversity may negatively affect patient care. Directed recruitment of underrepresented in medicine applicants has proven successful to increase diversity within training programs. Department websites had a more prominent role in virtual recruitment since the beginning of the COVID-19 pandemic. Features on these websites may be used to attract underrepresented in medicine applicants and increase diversity in a field. OBJECTIVE: This study aimed to analyze maternal-fetal medicine fellowship websites for the presence of diversity elements important to those people who are underrepresented in medicine. STUDY DESIGN: Fellowship websites were accessed in the summer of 2021. They were analyzed for the presence of 12 website elements that demonstrate commitment to diversity, including (1) nondiscrimination statement, (2) diversity and inclusion message, (3) diversity-specific language, (4) resources for trainees, (5) community demographics, (6) personalized biographies of faculty, (7) personalized biographies of fellows, (8) individual photographs of faculty, (9) individual photographs of fellows, (10) photos or biographies of alumni, (11) diversity publications, and (12) department statistics. Program size, region, and location were collected. Self-reported underrepresented in medicine data on residency programs was extracted from the National Graduate Medical Education Survey from 2019. Programs were dichotomized into ≥6 diversity elements. Nonparametric, chi-square, and Fisher exact tests were used for the analysis. RESULTS: Fellowship programs were analyzed (excluding military or fetal surgery [n=91/94]). Websites included a mean of 4.1±2.5 diversity elements. Most featured fewer than 6 elements (n=75 [82.4%]). When dichotomized to ≥6 diversity elements, larger faculty size was the only significant factor (P=.01). Most programs had fewer than 12 faculty members (n=54 [59.3%]), and only 9.3% of those programs had >6 diversity elements. In contrast, among programs with more than 12 faculty, 29.7% had ≥6 diversity elements. Faculty photos, fellow photos, and diversity publications were the most commonly featured items (92.4%, 68.1%, and 49.5%, respectively). The mean rate of underrepresented in medicine was 18.8%±11.3%, and no significant association was noted. There was a nonsignificant difference in diversity elements in the West United States with a mean of 5.3±2.2 diversity elements, compared with a mean of 3.7±2.0 diversity elements in the South United States. CONCLUSION: Fellowship websites convey information for trainees, especially in an era of virtual recruitment. This study highlights opportunities for directed improvements of websites for features that underrepresented in medicine trainees have identified as important.